Earthen masonry dwelling structures for extreme wind loads. (15th January 2015) - Matta, Fabio; Cuéllar-Azcárate, Mabel C.; Garbin, Enrico
Highlights: The strength demand of earthen masonry is computed for a dwelling structure. Wind loads are representative of hurricane and tornado effects. The parametric analysis accounts for different wall thicknesses and roof angles. Unreinforced stabilized earth masonry may be used for high-wind resistant dwellings. Internal reinforcement is necessary for safety shelter structures. Abstract: Earthen masonry made of compressed and stabilized earth blocks (CSEBs) is emerging as a sustainable and locally appropriate construction material for affordable high-quality dwellings. Compelling features include the local availability and affordability of suitable soils, thermal insulation and humidity control properties, and small embodied energy compared with fired clay masonry. The mechanical properties of CSEBs have been the subject of several investigations. However, the research on the response and design optimization of CSEB masonry building structures is in its infancy, and a significant knowledge and technological gap exists with regard to resistance to extreme loads due to natural hazards (e.g., high winds and earthquakes). It is necessary to address this gap to understand whether engineered earth masonry can be enlisted to respond to the growing demand for hazard-resistant dwellings that are also affordable and sustainable. This paper discusses the feasibility of using earth masonry in low-rise dwelling structures to withstand extreme winds. Hurricanes and tornadoes periodically scourge vast areas in Central and North America and the Caribbean where low-income families live, and where the demand for sustainable construction meets that for structural resistance and affordability. Feasibility is studied based on the structural analysis of the main wind force resisting system (MWFRS) of a typical one-story single-family dwelling subject to wind pressures resulting from 3-s gust speeds up to 90 m/s (324 km/h). The output consists of parametric curves that relate wind speed with masonry compressive, tensile and shear strength demand for wall thicknesses ranging from 203 to 508 mm. The structural adequacy of the MWFRS is assessed for the cases of flat and 15° gable roof. The design implications are discussed vis-à-vis strength reduction factors and design strength demands, and sustainable reinforcement options. It is concluded that it is feasible to design one-story CSEB masonry dwellings that can withstand winds loads from Category 4 hurricanes and EF3 tornadoes, provided that a rigid horizontal diaphragm is used. Grouted steel reinforcement may be used in safety shelter CSEB masonry structures to be designed for more extreme wind loads.